2018
DOI: 10.1016/j.humimm.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Circulating histocompatibility antigen (HLA) gene products may help differentiate benign from malignant indeterminate pulmonary lesions

Abstract: Soluble HLA molecules may have diagnostic value for early-stage NSCLC. Validation studies are currently underway using sera from a lung cancer screening cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…MHC class II expression in peripheral blood was also analyzed in lung cancer patients 34,4952. HLA-DR9 was found to have higher frequency in peripheral blood of lung cancer patients, while HLA-DR6 was found to have lower frequency in lung cancer patients than healthy controls by serological MHC typing 34.…”
Section: Mhc Class II Expression and Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…MHC class II expression in peripheral blood was also analyzed in lung cancer patients 34,4952. HLA-DR9 was found to have higher frequency in peripheral blood of lung cancer patients, while HLA-DR6 was found to have lower frequency in lung cancer patients than healthy controls by serological MHC typing 34.…”
Section: Mhc Class II Expression and Nsclcmentioning
confidence: 99%
“…Level of HLA-DQA1 28kDa band was significantly increased and HLA-DQA1 33-35kDa band was decreased in adenocarcinoma. These conclusions suggested that these molecules might be used for adenocarcinoma early diagnosis 52. However,the sample size of former research was not large and other pathological types of NSCLC should be included.…”
Section: Mhc Class II Expression and Nsclcmentioning
confidence: 99%
“…The previous study has uncovered that NM reversed IFN-γ-induced up-regulation of PD-L1 in lung cancer and pancreatic cancer cells (Figure 2) (66). The pivotal immune escape factor human leukocyte antigen-ABC (HLA-ABC) may help differentiate benign from malignant indeterminate pulmonary lesions (67). The study of Homma et al was confirmed that NM influenced IFN-γ-induced HLA-ABC up-regulation in lung cancer and pancreatic cancer (11), suggesting that NM may improve the treatment of immune resistant cancer.…”
Section: Discussionmentioning
confidence: 99%